2015
DOI: 10.1002/dneu.22366
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptors (nAChRs) at zebrafish red and white muscle show different properties during development

Abstract: Nicotinic acetylcholine receptors (nAChRs) are highly expressed at the vertebrate neuromuscular junction (NMJ) where they are required for muscle activation. Understanding the factors that underlie NMJ development is critical for a full understanding of muscle function. In this study we performed whole cell and outside-out patch clamp recordings, and single-cell RT-qPCR from zebrafish red and white muscle to examine the properties of nAChRs during the first 5 days of development. In red fibers miniature endpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
2
5
0
Order By: Relevance
“…The second evidence comes from the results obtained by patch-clamp recordings carried out at the endplate region of isolated mouse FDB fibres, where adenosine and the P1R agonist NECA significantly affected the NP o , the open frequency and the time constant of the adult nAChR channels. It is generally assumed that the kinetics of the MEPCs reflects the channel activity of the postsynaptic nAChRs (Katz and Miledi, 1973;Lu et al, 1993;Van der Kloot et al, 1994;Ahmed and Ali, 2016). In our control conditions, the rise and decay time of MEPCs were similar to those already reported elsewhere (Robertson and Wann, 1984;Tanzi and D Angelo, 1995;Petrov et al, 2009) and both values were significantly increased in the presence of adenosine.…”
Section: Discussionsupporting
confidence: 89%
“…The second evidence comes from the results obtained by patch-clamp recordings carried out at the endplate region of isolated mouse FDB fibres, where adenosine and the P1R agonist NECA significantly affected the NP o , the open frequency and the time constant of the adult nAChR channels. It is generally assumed that the kinetics of the MEPCs reflects the channel activity of the postsynaptic nAChRs (Katz and Miledi, 1973;Lu et al, 1993;Van der Kloot et al, 1994;Ahmed and Ali, 2016). In our control conditions, the rise and decay time of MEPCs were similar to those already reported elsewhere (Robertson and Wann, 1984;Tanzi and D Angelo, 1995;Petrov et al, 2009) and both values were significantly increased in the presence of adenosine.…”
Section: Discussionsupporting
confidence: 89%
“…Although the distinct compositions between fast and slow muscle AChR subunits were recently described (13), the mechanism remains unresolved. Ahmed and Ali reported that slow muscles expressed mRNA of  and  subunits (35). The absence of alternate subunit composition reported here also strongly supports the idea on July 31, 2020 http://advances.sciencemag.org/ Downloaded from that the subunit composition is regulated at the posttranslational level.…”
Section: Discussionsupporting
confidence: 88%
“…We had previously found that the decay time course of mEPCs recorded from white fibers of 2 dpf embryos was bi-exponential in nature due to the presence of multiple classes of nAChRs 32 , 33 . Because changes in the kinetics often signify a change in the subunit composition of synaptic receptors, we examined the exponential decay of mEPCs but found that there was no significant difference amongst any of the treatments (Fig.…”
Section: Resultsmentioning
confidence: 99%